Fitoplancton de una laguna vegetada por Eichbornia crassipes en el valle de inundación del río Paraná (Argentina) - Zolacar de Domitrovic, Yolanda (Ambiente Subtropical, 2023)
Composition, diversity, abundarles and distríbution of a community of phytoplankton were studied since June 1982 to January 1985. An extraordinary flood occurred within that period in the a rea. The waterbody was partially covered by water hyacinth (Eichhomia crassipes). One or two samples were taken by month in vegetated and non-vegetated areas. Cell counts were done by the Utermóhl method (1958). The results shown an inverse relationship among river hydrometric level and pond depth in relation to phytoplankton density. the lowest density was always founded in open water during flooded phases; Aulacoseira granúlate and some Chlorococcales were the most representativa. The population density was higher during the lowest water and isolation phase (between 2303 and 15500 ind/ml). Monoraphidium tort/fe, Crudgenia quadrata, Coelastrum pseudomicroporum, Scenedesmus disdformis, Sphaemcystis schroeteri and Dictyosphaerium ehrenbergianum were the species dominant. The highest diversity was observad in the decreasing water level and isolated phase species dominant. The highest diversity was observad in the decreasing water leve) and isolated phase after an extraordina- ry flood. The abundance and richness of species was highest in the vegetated area. The more frecuent taxa were: Cryptophyceae, Chlorophyceae (Chloro- coccales), Euglenophyceae and Bacillariophyceae. The abundance of Cryptophyceae was significant between vegetated and non vegetated area (t = 3.031; P < 0.01; g.l. = 8). The remainder species of algae were not significant between both areas. Vertical distríbution of density and diversity were more homogeneous during high waters and heterogeneous during low waters. Abundance of phytoplankton was positively correlated with temperature (r = 0.375; P < 0.01) and negatively correlated with hydrometric leve) (r = -0.693; P < 0.001) and depth of pond (r = -5.20; P < 0.001).